Impacts Of Ethno-Religious Crisis On Settlement Patterns, Socialization And Social Studies Students’ Achievement At The University Of Jos, Nigeria - Shitu Lukman Olayinka (Britain International for Academic Research (BIAR) Publisher, 2023)
This study investigated the impact of ethno-religious crisis on settlement patterns and social studies students’ socialization at the University of Jos. With the volatility of Jos the capital of Plateau state to ethno-religious crisis it becomes pertinent to investigate issues of ethno-religious crisis and how it impacted on student’s settlement patterns and social life within Jos metropolis. The study employed a cross sectional survey research design. The study made use of undergraduate social studies students for the academic session 2020/2021. A sample of 200 students were selected using proportional random sampling technique and the sample was cut across 100 level to 400level with both gender given equal consideration. The data used for the study were collected using a structured questionnaire which was subjected to face and content validity of experts. The data collected were analysed through using both descriptive and inferential statistic. The study findings revealed that, ethno-religious crisis affects settlement patterns of students in Jos North and has caused the redrawing of Jos map. This also affects freedom of socialization as students are restricted from moving through some environments that is perceived as dangerous, this erroneous belief could affect students achievement adversely. The study recommended that, there should be adequate hostels to accommodate students within the campuses so that students will not be exposed to the risk of ethno-religious crises outside the campus. Also, government should provide needed atmosphere in terms of policy and flexible framework that will ensure peaceful co-existence among others.